Seni Dalam Mengelola Kelas Melalui Prosedur Perencanaan, Pelaksanaan, dan Evaluasi Guna Menciptakan Kelas yang Hebat - Mustikaati, Wina; Ambarwati, Desti Noer; H, Herlina; Nurbaiti, Elsa Frida; Al Rashid, Reyqi Favian (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In education, the classroom plays an important role in determining the quality of education. Educators have a big responsibility to manage the class and overcome students’ learning boredom. Effective classroom management is an art that teachers must master to create an optimal learning environment, a dynamic classroom and support the development of learners’ potential. Classroom management involves three main stages: classroom management procedures, planning and evaluation. Classroom management procedures include setting goals, methods, and resources needed. Planning includes plans to achieve the set goals. Evaluation, aims to assess the effectiveness of the learning process to improve the quality of education in schools. This research aims to provide insight into classroom management through three stages to achieve a great classroom. The research method used is a literature study with a qualitative approach, with data collected and analyzed from various written sources relevant to the discussion. The results showed that teachers can manage the class by understanding the condition of the class, utilizing learning media, arranging the learning environment, using appropriate learning strategies, and assisting in providing motivation. With these steps, it is hoped that the learning process can take place effectively and efficiently, so as to create a great class.